Optimization Model of Tourism Android Application Based on Madura Local Wisdom as a Persuasive digitalization for Global Tourists - Sri Wahyuningsih; Mohammad Arief Wahyudi (Jurnal Spektrum Komunikasi, 2024)
Madura has natural, cultural, religious, and culinary attractions, this adds to the wealth of local wisdom of Madura to attract visitors from outside Madura. Bangkalan Regency itself has a lot of tourism, currently still under development by each village pokdarwis (kelompok sadar wisata) and assisted by the local tourism office, but this is not optimal. Such as tourism development through promotion and optimization has not been maximized. Looking at the background, the researcher wants to know, analyze, and dig deeply: 1) the Optimalization model of the application in Android destination-based traveler local wisdom as media persuasive for tourism global, 2) Why optimization of application in Android destination-based traveler local wisdom as digitalization persuasive for the important tourism global development. The subjects are village tourism managers, village heads, and tourism offices. The objects of the optimization in application android destination-based traveler local wisdom as persuasive digitalization for tourism global. Data collection methods through observation, in-depth interviews, documentation, audio-visual materials, and literature. The case study approach and the validity use data triangulation, methods, and member checks. The results of the research: 1) produced an optimization model of local wisdom-based tourist destination in android applications as persuasive media for global tourists, 2) importance of a tourism android application, to introduce potential Natural Beach Tourism, introduce potential artificial beach tourism, introduce superior religious tourism, introduce superior cultural tourism, introduce superior culinary tourism, increase the creative economy through local wisdom-based tourism, and provide information on village tourism that has the potential to become a leading tourism in Base.